PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP KINERJA PERUSAHAAN DENGAN INTELLECTUAL CAPITAL SEBAGAI VARIABEL MODERASI - Risa Martia Aryanti; Susi Retna Cahyaningtyas; Iman Waskito (Fakultas Ekonomi dan Bisnis Unram, 2021)
The study aims to determine the effect of enterprise risk management on company performance with intellectual capital as a moderating variable. The dependent variable of company performance is measured by ROE. Enterprise risk management independent variables measured content analysis based on the 2017 COSO ERM framework in the form of 20 principles that include 5 components. Intellectual capital moderation variable is measured by VAICTM. This research uses the signaling theory. The sample was obtained based on purposive sampling and produced 43 companies in property, real estate and building construction companies for the 2015-2019 fiscal year which were listed on the Indonesia Stock Exchange. Data were analyzed based on Moderating Regression Analysis (MRA). The results of this study indicate that enterprise risk management has no effect on company performance which shows the coefficient of ERM is negative, that is -0.965 with a probability of 0.336> 0.05. This result also shows that intellectual capital does not moderate the relationship between enterprise risk management and company performance, which shows the coefficient value of -0.047 with sig. 0.962.